Tópicos de geometria diferencial - Batista, Ricardo Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
O principal objetivo deste trabalho é confeccionar um texto para alunos de gradua ção na área de Ciências Exatas e da Terra concernente ao estudo da Curvatura Gaussiana e Aplicação de Gauss, Superfícies Mínimas, Teorema Egregium de Gauss e o Teorema de Gauss- Bonnet para curvas simples fechadas

The main objective from this work is to make a text for students of graduation in the area of exact sciences and of the land concerning to the study of the Gaussian Curvature and the Gauss Map, Minimal Surfaces, Gauss's Theorem Egregium and the Gauss-Bonnet Theorem for Simple Closed Curves
Keywords: Geometria diferencial; Superficies minimas; Aplicação de Gauss; Curvatura gaussiana; Teorema Egregium de Gauss; Teorema de Gauss Bonnet; Gauss map; Gaussian curvature; Minimal surfaces; Gauss's theorem Egregium; Gauss-Bonnet theorem